2009
DOI: 10.1016/j.nbt.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Control of plant diseases with secondary metabolite of Clitocybe nuda

Abstract: Culture filtrates of five strains of Clitocybe nuda displayed various degrees of antimicrobial activity against plant pathogenic fungi and/or bacteria tested. The culture filtrate of C. nuda strain LA82 was very effective in reducing the incidence of Phytophthora blight of pepper caused by Phytophthora capsici and the incidence of leaf spot on pepper caused by Xanthomonas axonopodis pv. vesicatoria. The inhibitory substance in the C. nuda strain LA82 culture filtrate was stable at low and high pH. It was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This result suggested that substances produced by C. nuda had the ability to suppress Pythium damping-off. The inhibitory effects of culture filtrates of C. nuda on the growth of plant fungal and bacterial pathogens have been demonstrated in previous studies (Chen & Huang 2009). The antimicrobial compounds of C. nuda against Phytophthora capsici have been identified as 2methoxy-5-methyl-6-methoxymethyl-p-benzoquinone, indole-3-carbaldehyde and 6-Hydroxy-2Hpyran-3-carbaldehyde (Chen et al 2012).…”
Section: Discussionmentioning
confidence: 74%
“…This result suggested that substances produced by C. nuda had the ability to suppress Pythium damping-off. The inhibitory effects of culture filtrates of C. nuda on the growth of plant fungal and bacterial pathogens have been demonstrated in previous studies (Chen & Huang 2009). The antimicrobial compounds of C. nuda against Phytophthora capsici have been identified as 2methoxy-5-methyl-6-methoxymethyl-p-benzoquinone, indole-3-carbaldehyde and 6-Hydroxy-2Hpyran-3-carbaldehyde (Chen et al 2012).…”
Section: Discussionmentioning
confidence: 74%
“…To estimate the molecular weight of the inhibitory substance, 5 ml of the extract was placed in a molecular porous membrane tubing with molecular weight cut-off of 100, 500, 1000 or 10,000 (Spectrum Medical Industries Inc., Los Angeles, CA), dialyzed at 24 8C against 1000 ml distilled water changed three times over a 24-h period, and used for germination tests [20].…”
Section: Characterization Of the Inhibitorsmentioning
confidence: 99%
“…Also, culture filtrate of Clitocybe nuda (an edible mushroom) was very effective in reducing the incidence of Phytophthora blight and leaf spot on pepper caused by Phytophthora capsici and Xanthomonas axonopodis pv. vesicatoria, respectively (Chen and Huang 2009). The culture filtrate of Trichothecium roseum MML003 strongly inhibited the mycelial growth and sclerotial formation of the rice sheath blight pathogen, Rhizoctonia solani (Jayaprakashvel et al 2010).…”
Section: Introductionmentioning
confidence: 98%